2022
DOI: 10.52312/jdrs.2022.676
|View full text |Cite
|
Sign up to set email alerts
|

Comparative finite element analysis of four different internal fixation implants for Pauwels type III femoral neck fractures in various fracture angles in the sagittal plane

Abstract: Objectives This study aimed to evaluate the performance of four different fixation techniques for Pauwels type III femoral neck fractures considering the fracture morphology in the sagittal plane. Materials and methods We constructed three different fracture morphologies in the sagittal plane in Pauwels type III femoral neck fractures: posteriorly angled at 20°, neutral, and anteriorly angled at 20°. We set up four fixation devices, including three cannulated screws (3C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The elderly population often presents with various underlying diseases, reduced bone strength, increased fragility, and declining physical function. Conventional conservative or internal fixation treatments may not achieve satisfactory results 3,4 . In recent years, clinical reports have suggested that total hip arthroplasty is an effective treatment for femoral neck fractures in the elderly, allowing for good treatment outcomes, rapid recovery of limb function, reduced occurrence of complications, and decreased risk of secondary surgery associated with the internal fixation treatment 5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elderly population often presents with various underlying diseases, reduced bone strength, increased fragility, and declining physical function. Conventional conservative or internal fixation treatments may not achieve satisfactory results 3,4 . In recent years, clinical reports have suggested that total hip arthroplasty is an effective treatment for femoral neck fractures in the elderly, allowing for good treatment outcomes, rapid recovery of limb function, reduced occurrence of complications, and decreased risk of secondary surgery associated with the internal fixation treatment 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Conventional conservative or internal fixation treatments may not achieve satisfactory results. 3,4 In recent years, clinical reports have suggested that total hip arthroplasty is an effective treatment for femoral neck fractures in the elderly, allowing for good treatment outcomes, rapid recovery of limb function, reduced occurrence of complications, and decreased risk of secondary surgery associated with the internal fixation treatment. 5,6 However, there is currently no consensus on the choice of artificial hip joint prosthesis in clinical practice, with the primary focus being on the selection between cemented and uncemented prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Due to poor biomechanical stability and failure to bear weight early after surgery, patients may have refracture, internal fixation failure, and ischemic necrosis of the femoral head. [3] In particular, once the femoral head necrosis occurs, it would be an irreversible complication and, therefore, the femoral head ischemic necrosis is also known as the deathless cancer. [4] Currently, the prognosis is usually evaluated according to different types of femoral neck fractures.…”
mentioning
confidence: 99%
“…The finite element analysis (FEA) is frequently used in the biomechanical analysis of orthopedic implants. [14][15][16][17][18][19] It has previously been used to investigate the effects of different designs of CHPs on the acromion and clavicle. [14][15][16] In the present study, in addition to the model created using the standard hook plate, we constituted a new model with an additional cortical screw placed in the coracoid process through the third hole of the hook plate (CC screw) and aimed to investigate the stresses on the hook of the plate in both models with FEA.…”
mentioning
confidence: 99%